Pengaruh Kombinasi Senyawa Humik dan CaCO3 terhadap Alumunium dan Fosfat Typic Paleudult Kentrong Banten - Sugeng Winarso; Eko Handayanto; Syekhfani Syekhfani; Didik Sulistyanto (UNIVERSITY OF LAMPUNG, 2009)
Effect of Humic Compounds and CaCO3 Combination on Aluminium and Phosphate of Typic Paleudult Kentrong Banten (S. Winarso, E. Handayanto, Syekhfani and D. Sulistyanto): Decomposition of organic matter releases humic compounds, that can chelate metals include Al in acidic soils. This chelation of Al is important for decreasing of Al activity and P fixation in acidic soils. This study was aimed to test the effect of humic compounds extracted from rice-straw compost and CaCO3 combination on aluminium activity and phosphate (available P) on an Ultisol (Typic Paleudult) collected from Kentrong Banten. A laboratory study was conducted by series consentration of CaCO3 (0, 500, 1.000, 2.000, dan 3.000 ppm) in 8 grams of acidic soil. The acidic soil had previously been subjected to continuously addition of humic compounds and none. Then, these mix of soil and CaCO3 were added 40 ml contained 5.000 ppm humic compounds to obtain 1:5 soil:suspension ratio and control was made by using aquadest. They were shaked for 2 hours every day and pH was measured. At 11st days incubation Alexch (N KCl) and soluble of P (PB and PC) were measured. The results showed that liming or addition of CaCO3 to the acidic soils decreased Alexch (precipitated to be Al(OH)3) linearly with formula y = -0.778x + 6.108; y = Alexch (Cmol kg-1), x = CaCO3 (M); R² = 0,916. Combination addition of humic compounds and CaCO3 was able to increase pH and Alexch up to not detected. The increased of P-soluble or desorption P untill 384% took place at addition of 0.0016 M CaCO3 and 5000 ppm humic compounds. More desorption of P was observed if the acidic soils has previously been subjected to continuously addition of humic compounds, such us the increased of soluble P up to 739% at addition of CaCO3 0.0008 M.